Efektivitas Pengembangan Paket Pembelajaran Berbasis Proyek dengan Kerangka Kerja TPACK pada Materi Keanekaragaman Hayati - Syam, Dewi Astuti; Ismail; Patongai, Dian Dwi Ulan Sari (Universitas Islam Riau (UIR) Press, 2023)
The Effectiveness of Developing Project-Based Learning Packages with the TPACK Framework on Biodiversity Materials . This study aims to determine the effectiveness of the results of developing project-based learning packages using the TPACK framework. This research was conducted at SMAN 08 Makassar in class X using the Pretest Posttest Control Group Design research design. This Project-Based Learning Package with the TPACK Framework is motivated by the lack of innovative teaching materials that are relevant to developments in the 21st century. This type of research is development research (R & D) and uses the 4D model development model. 4D stages consist of 4, namely (1) Define, (2) Design, (3) Develop, (4) Disseminate. The learning packages have gone through the validation and practicalization stages with very satisfactory grades and are therefore suitable for use in learning process activities in the classroom, followed by testing the effectiveness of implementing project-based learning packages with the TPACK framework on this biodiversity material. Judging from the test scores of student learning outcomes, it is known that the learning packages that have been developed are effective with a score of 92.1%. Based on these results, it can be concluded that the development of Learning Packages is valid, practical, and effective.